2009
DOI: 10.1159/000231567
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Analyses and Mutation Screening of the <i>SLC26A4</i> and <i>FOXI1</i> Genes in 101 Taiwanese Families with Bilateral Nonsyndromic Enlarged Vestibular Aqueduct (DFNB4) or Pendred Syndrome

Abstract: Recessive mutations in the SLC26A4 gene are responsible for nonsyndromic enlarged vestibular aqueduct (EVA) and Pendred syndrome. However, in some affected families, only 1 or 0 mutated allele can be identified, as well as no clear correlation between SLC26A4 genotypes and clinical phenotypes, hampering the accuracy of genetic counseling. To elucidate the genetic composition of nonsyndromic EVA and Pendred syndrome, we screened related genomic fragments, including the SLC26A4 coding regions, the SLC26A4 promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 54 publications
2
52
1
2
Order By: Relevance
“…Yang et al described several EVA patients with a heterozygous SLC26A4 mutation in combination with a heterozygous hypo-functional variant of FOXI1 [51] or KCNJ10 [52]. However, these results have not been obtained in other studies of EVA cohorts [53][54][55] and the pathogenic potential of the reported FOXI1 and KCNJ10 variants remains uncertain [56,57].…”
Section: Etiology Of Eva In Patients With Nondiagnostic Slc26a4 Genotmentioning
confidence: 99%
“…Yang et al described several EVA patients with a heterozygous SLC26A4 mutation in combination with a heterozygous hypo-functional variant of FOXI1 [51] or KCNJ10 [52]. However, these results have not been obtained in other studies of EVA cohorts [53][54][55] and the pathogenic potential of the reported FOXI1 and KCNJ10 variants remains uncertain [56,57].…”
Section: Etiology Of Eva In Patients With Nondiagnostic Slc26a4 Genotmentioning
confidence: 99%
“…Previously, it was suggested that a second undetected mutant allele of SLC26A4 in Caucasian M1 EVA subjects would encode some residual pendrin, leading to a less severe phenotype than the M2 EVA group [Choi et al, 2009a-c]. However, it is possible that this genotype-phenotype correlation does not apply to East Asian populations since some studies in these populations failed to delineate the same genotype-phenotype correlation [Miyagawa et al, 2014;Wu et al, 2010]. These studies showed a similar severity of clinical features between the M1 and M2 groups .…”
Section: Discussionmentioning
confidence: 99%
“…The autosomal recessive inheritance of PDS and DFNB4 is well established and yet, for many affected individuals, analysis of the coding sequences and splice sites of the SLC26A4 gene PrePrints has failed to identify one or both of the mutations required to cause these disorders (Campbell et al, 2001;Tsukamoto et al, 2003;Pryor et al, 2005;Albert et al, 2006;Yang et al, 2007;Wu et al, 2010). In fact, an analysis of six studies with a total enrollment of 769 hearing impaired probands with EVA, a non-pathognomonic clinical finding that is a hallmark of PDS and DFNB4, reveals that only 25% have biallelic SLC26A4 mutations ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis of published studies in PrePrints which FOXI1 and KCNJ10 were sequenced in SNHL patients with inner ear malformations does not support these frequencies ( the initial studies that implicated the genes in the digenic inheritance of PDS/DFNB4 (Yang et al, 2007;Yang et al, 2009). However, the actual contribution of FOXI1 and KCNJ10 mutations to SNHL may be more limited, as illustrated by several subsequent studies in which either no FOXI1 variants (Wu et al, 2010;Mercer, Mutton & Dahl, 2011;Lai et al, 2012;Chen et al, 2012;Chai et al, 2013), or no KCNJ10 variants (Mercer, Mutton & Dahl, 2011;Chen et al, 2012) were identified.…”
Section: Discussionmentioning
confidence: 99%